Implementation of Occupational Safety and Health at PT Menarini Indria Laboratories Bekasi - Ginza, Rio; Sukwika, Tatan (Journal of Applied Management Research, 2024)
PT Menarini Indria Laboratories, a foreign pharmaceutical company in Indonesia, recognizes the importance of occupational safety as a critical step toward operational success. A significant focus on the Quality Control (QC) division and the Quality Control Laboratory, where drug quality testing is conducted, presents potential hazards to employees. Through the implementation of ISO 45001:2018 Standard, the company demonstrates its commitment to occupational safety and health. The results showed an excellent level of ISO 45001:2018 implementation with percentage values above 78% for each step of the PDCA cycle. Hazard Identification and Risk Assessment (HIRA) analysis helped identify potential hazards and risks in QC. Some areas, such as the use of heavy equipment, chemical spills, and laboratory operations, showed a level of risk that needed to be managed appropriately. The company has implemented appropriate controls, such as SOPs, ergonomics training, use of assistive devices, and personal protection (PPE). Proactive measures such as the Zero Accident Program and annual external audits are also implemented to achieve safety goals. Nonetheless, the company must continuously monitor and improve its safety management system to ensure a safe, efficient, and compliant working environment. By aligning ISO 45001:2018 implementation and risk mitigation strategies, PT Menarini Indria Laboratories can ensure continued operational success while providing optimal protection for its workforce.